1979
DOI: 10.1007/bf02441170
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the density and tensile strength of human femoral cortical bone

Abstract: In order to ascertain whether the intrinsic strength of human bone changes with age or not, we have determined the ultimate tensile strength and density of strips of femoral cortical bone. These femora were collected from cadavers varying in age from 13 to 97 years. The results show that both density and intrinsic strength of bone increase up to about the fourth decade of life and then decrease with age. However, the rate of decrease of strength is greater than that of density. This indicates that the density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 11 publications
1
47
0
Order By: Relevance
“…Send offprint requests to S. Chatterji, Teknologisk Inst., T~tstrup, Denmark. rate of decrease of tensile strength is higher than the rate of decrease in density [1]. It would thus appear that the loss of tensile strength of human bone with advancing age could not be fully accounted for by a decrease in density.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Send offprint requests to S. Chatterji, Teknologisk Inst., T~tstrup, Denmark. rate of decrease of tensile strength is higher than the rate of decrease in density [1]. It would thus appear that the loss of tensile strength of human bone with advancing age could not be fully accounted for by a decrease in density.…”
mentioning
confidence: 96%
“…It has previously been observed that after the third decade of life the tensile strength of bone decreases faster than its density [1], indicating that some microstructural change occurs in bone with advancing age. In order to try to elucidate this observation, the orientation and particle size of the mineral phase of bone have been studied with respect to age.…”
mentioning
confidence: 98%
“…The responses of subchondral bone to joint loading are not completely understood, but it appears to respond in a manner similar to other bony tissues (Radin and Paul, 1971;Simon et al, 1972;Eckstein et al, 1995;Murray et al, 2001;Burr and Radin, 2003), and while bone mineral density is largely influenced by heredity (Krall and DawsonHughes, 1993), other environmental factors such as exercise play significant roles (e.g., Forwood and Burr, 1993;Magkos et al, 2007). Increasing bone density confers several advantages, such as increased strength in compression, compressive modulus, fatigue life, resistance to crack initiation, and tensile strength (Carter and Hayes, 1977;Wright and Hayes, 1977;Wall et al, 1979;Currey, 1988Currey, , 2002Rice et al, 1988).…”
mentioning
confidence: 99%
“…The most common bone studied is the femur. Quasistatic and dynamic tensile and bending tests of human femoral cortical bone have determined that the femur responds with increasing strength and stiffness from youth to the third or fourth decade and then decreases [106,150,[202][203][204][205][206]. Specifically, tensile tests have revealed that pediatric femur tissue has a low modulus of elasticity, lower ash content, and absorbs more energy to fracture than the adult femurs [207].…”
Section: Biomechanical Studiesmentioning
confidence: 99%